Eye Drop Instillation of the Rac1 Modulator CNF1 Attenuates Retinal Gliosis and Ameliorates Visual Performance in a Rat Model of Hypertensive Retinopathy. (15th July 2019) - Matteucci, Andrea; Ricceri, Laura; Fabbri, Alessia; Fortuna, Andrea; Travaglione, Sara; Guidotti, Marco; Martinelli, Andrea; Villa, Marika; Pricci, Flavia; Maroccia, Zaira; Campana, Gabriele; Malchiodi-Albedi, Fiorella; et al.
Abstract: In hypertensive retinopathy, the retinal damage due to high blood pressure is accompanied by increased expression of Glial Fibrillary Acidic Protein (GFAP), which indicates a role of neuroinflammatory processes in such a retinopathy. Proteins belonging to the Rho GTPase family, particularly Rac1, are involved in the activation of Müller glia and in the progression of photoreceptor degeneration, and may thus represent a novel candidate for therapeutic intervention following central nervous system inflammation. In this paper, we have observed that topical administration as eye drops of Cytotoxic Necrotizing Factor 1 (CNF1), a Rho GTPase modulator, surprisingly improves electrophysiological and behavioral visual performances in aged spontaneously hypertensive rats. Furthermore, such functional improvement is accompanied by a reduction of Rac1 activity and retinal GFAP expression. Our results suggest that Rac1 inhibition through CNF1 topical administration may represent a new strategy to target retinal gliosis. Highlights: Rac1 may represent a novel candidate for therapeutic intervention following retinopathy. CNF1 improves electrophysiological and behavioral visual performances in aged spontaneously hypertensive rats. CNF1 topical administration, through Rac1 inhibition, may constitute a new therapeutic approach to target retinal gliosis.